2002
DOI: 10.1017/s0265051702000141
|View full text |Cite
|
Sign up to set email alerts
|

Raising students' performance in music composition through the use of information and communications technology (ICT): a survey of secondary schools in England

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0265051702000141How to cite this article: Adrian Pitts and Robert Mawuena Kwami (2002). Raising students' performance in music composition through the use of information and communications technology (ICT): a survey of secondary schools in England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 5 publications
3
18
0
Order By: Relevance
“…Evidence from both the open-ended questions and the analyses of both verbal and nonverbal responses in the retrospective verbal protocols corroborates the results of Pitts and Kwami (2002) and Gall and Breeze (2005) to confirm that all the participants worked with enthusiasm on the task. They also enjoyed the immediacy of their work and the professional sound of the music as it was played back.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Evidence from both the open-ended questions and the analyses of both verbal and nonverbal responses in the retrospective verbal protocols corroborates the results of Pitts and Kwami (2002) and Gall and Breeze (2005) to confirm that all the participants worked with enthusiasm on the task. They also enjoyed the immediacy of their work and the professional sound of the music as it was played back.…”
Section: Discussionsupporting
confidence: 70%
“…As a musical medium Dance eJay has 'real music appeal' in so far as it uses professionally edited original sound samples in the style specific genre of 'Dance' music. This notion of the music sounding 'real' is corroborated in the research of Gall and Breeze (2005), Pitts and Kwami (2002). They also found that the participants in their study worked with enthusiasm using 'existing tunes' and 'liked the immediacy of their work and the ''professional'' sound when it was played back' (Pitts and Kwami 2002, 66).…”
Section: Introductionmentioning
confidence: 61%
“…Evidence from both the open-ended questions and the analyses of both verbal and non-verbal responses in the RVP's corroborates the results of Pitts and Kwami (2002) to confirm that all the participants worked with enthusiasm on the task. They also enjoyed the immediacy of their work and the professional sound of the music as it was played back.…”
Section: Discussionsupporting
confidence: 71%
“…Marshall brought about the creation of virtual learning environments in which no formal 'teacher' is present (Salavuo 2006), and yet through appraising and evaluating the musical products of others and presenting their own musical products within a virtual environment, young people are now able to 'perform' their compositions to a wide and international virtual audience. Although some evaluation has taken place of the learning styles and processes which take place within these environments (Johnson 2001;Pitts and Kwami 2002;Sanctisde et al 2003;De Souza and Preece 2004;Plant 2004;Ridings and Gefen 2004;Salavuo 2006); this represents a relatively under-researched area of music technology.…”
Section: Music and Technologymentioning
confidence: 99%